Penerapan Vector Space Model Dalam Klasifikasi Penilaian Thematic Appeception Test - Nurhasan, Usman; Arianto, Rakhmat; Kurnia, Alwan Ghozi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Psychology is the study of human mental behavior and functions scientifically. In practice, a person's personality can be assessed from psychological tests. One of the psychological tests is the Thematic Apperception Test (TAT). TAT Test is a projective psychological test consisting of various themes presented in the form of an image which is then projected accordingly with the response. The purpose of the TAT is to reveal the dynamics of the subject's personality in the form of encouragement, sediment, complex, and various dominant conflicts. Thematic Apperception Test still uses a card and tape recorder to record Testee's voice. Calculation of results or assessments is still done manually. Errors in the assessment will affect the results, so we need an intelligent information system using the vector space model method based on experience in the field of psychology. A web-based system which can provide personality test results and information about the Thematic Apperception Test. From the test results using 10 stories, it was found that the average precission value was 72.7%, the average recall value was 86.7%, and the average f-measure value was 78.3%.